Dysbiosis-Induced Secondary Bile Acid Deficiency Promotes Intestinal Inflammation - Sinha, Sidhartha R.; Haileselassie, Yeneneh; Nguyen, Linh P.; Tropini, Carolina; Wang, Min; Becker, Laren S.; Sim, Davis; Jarr, Karolin; Spear, Estelle T.; Singh, Gulshan; Namkoong, Hong; Bittinger, Kyle; et al. (Cell host & microbe, 2020)
Secondary bile acids (SBAs) are derived from primary bile acids (PBAs) in a process reliant on biosynthetic capabilities possessed by few microbes. To evaluate the role of BAs in intestinal inflammation, we performed metabolomic, microbiome, metagenomic, and transcriptomic profiling of stool from ileal pouches (surgically created resevoirs) in colectomy-treated patients with ulcerative colitis (UC) versus controls (familial adenomatous polyposis [FAP]). We show that relative to FAP, UC pouches have reduced levels of lithocholic acid and deoxycholic acid (normally the most abundant gut SBAs), genes required to convert PBAs to SBAs, and Ruminococcaceae (one of few taxa known to include SBA-producing bacteria). In three murine colitis models, SBA supplementation reduces intestinal inflammation. This anti-inflammatory effect is in part dependent on the TGR5 bile acid receptor. These data suggest that dysbiosis induces SBA deficiency in inflammatory-prone UC patients, which promotes a pro-inflammatory state within the intestine that may be treated by SBA restoration. [Display omitted] •Secondary bile acids (SBAs) are reduced in UC pouch patients, relative to FAP patients•Reduced Ruminococcaceae in UC pouches is associates with SBA deficiency•SBA supplementation ameliorates inflammation in animal models of colitis•The protective effect of SBAs is in part dependent on the TGR5 bile acid receptor Secondary bile acids (SBAs) are some of the most concentrated bacterially derived gut metabolites. Sinha et al. find UC pouch patients have reduced SBAs and Ruminococcaceae (one of the few SBA-producing taxa) compared with FAP-control patients. In colitis models, SBAs ameliorate disease in a process reliant on the TGR5 bile acid receptor.